2019
DOI: 10.1007/s13042-019-01041-1
|View full text |Cite
|
Sign up to set email alerts
|

Study on the prediction of stock price based on the associated network model of LSTM

Abstract: Stock market has received widespread attention from investors. It has always been a hot spot for investors and investment companies to grasp the change regularity of the stock market and predict its trend. Currently, there are many methods for stock price prediction. The prediction methods can be roughly divided into two categories: statistical methods and artificial intelligence methods. Statistical methods include logistic regression model, ARCH model, etc. Artificial intelligence methods include multi-layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(94 citation statements)
references
References 11 publications
1
50
0
5
Order By: Relevance
“…On the other hand, the experimental results of the LSTM model, with an added layer, according to Pang et al [26], showed a high level of prediction accuracy for the composite stock model (56.9%, and 52.4% for individual stocks). Other results unambiguously confirm the efficiency of LSTM, for example, in the case of predicting the volatility of and time jumps in financial series within an analysis of 11 global stock markets [27], or in the case of predicting the development of stock markets according to Ding and Qin [28], whose model of associated LSTM showed a prediction accuracy of more than 95%. Chebeir et al [19] achieved a similar result when it came to predicting stock volatility using LSTM.…”
Section: Literature Reviewsupporting
confidence: 59%
“…On the other hand, the experimental results of the LSTM model, with an added layer, according to Pang et al [26], showed a high level of prediction accuracy for the composite stock model (56.9%, and 52.4% for individual stocks). Other results unambiguously confirm the efficiency of LSTM, for example, in the case of predicting the volatility of and time jumps in financial series within an analysis of 11 global stock markets [27], or in the case of predicting the development of stock markets according to Ding and Qin [28], whose model of associated LSTM showed a prediction accuracy of more than 95%. Chebeir et al [19] achieved a similar result when it came to predicting stock volatility using LSTM.…”
Section: Literature Reviewsupporting
confidence: 59%
“…and, 2) practical: investment strategies (Blitz and Van Vliet, 2007), portfolio management (Hocquard et al, 2013), and beyond the world of finance (Erb et al, 1994;Rich and Tracy, 2004). Financial models conventionally focused on technical analysis (TA) relying only on numerical features like past prices (Ding and Qin, 2019;Nguyen et al, 2019) and macroeconomic indicators like GDP (Hoseinzade et al, 2019). Such TA methods include discrete: GARCH (Bollerslev, 1986), continuous (Andersen, 2007, and neural approaches (Nguyen and Yoon, 2019;Nikou et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…The second type of work (Association), uses the Associated Network algorithm to expose model associations in stock market predictions [30], this association method can be used to find relationships between signals that appear in technical indicators in stock predictions. which will be bullish.…”
Section: Using a Clustering Algorithm Shares Will Be Grouped Against An Investment Decision Making Criterion (Clustering)mentioning
confidence: 99%